2004
DOI: 10.1002/crat.200410320
|View full text |Cite
|
Sign up to set email alerts
|

The use of analytical peak profile functions to fit diffraction data of planar faulted layer crystals

Abstract: The implication of the use of particular peak profile functions in the fit of diffraction data on the nature and density of stacking faults in layered solids is studied. Common type of profile functions are studied: Gauss, Lorentz, pseudoVoigt and Pearson VII. An additional peak profile is introduced. For each profile function the decaying term of the probability correlation function is determined and the expression for the correlation length is deduced. The form of the asymmetric component of each profile is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In sample with Cr/Ni thickness ratio 0.6, at 2Â degrees 41.56 • , 43.65 • and 65.19 • , there are peaks which correspond to -Cr 3 Ni 2 were observed. Also, the peak at 43.43 • was deconvoluted with a technique which was described elsewhere and the exact peak location of -Cr 3 Ni 2 was calculated as 43.65 • [24]. As a result, it was revealed that -Cr 3 Ni 2 was observed as major phase in sample with Cr/Ni thickness ratio 0.6.…”
Section: Resultsmentioning
confidence: 99%
“…In sample with Cr/Ni thickness ratio 0.6, at 2Â degrees 41.56 • , 43.65 • and 65.19 • , there are peaks which correspond to -Cr 3 Ni 2 were observed. Also, the peak at 43.43 • was deconvoluted with a technique which was described elsewhere and the exact peak location of -Cr 3 Ni 2 was calculated as 43.65 • [24]. As a result, it was revealed that -Cr 3 Ni 2 was observed as major phase in sample with Cr/Ni thickness ratio 0.6.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks are rather symmetric. ‘Super‐Lorentzian' profiles are often observed with faulted structures, in which cases twin faults happen to cause symmetric tails . Using fit parameters found for the (111) reflection, the ratio of the intensity of the broad composite peak attributed to PFs (I111p.f.) relative to the total peak intensity (I111) was calculated .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that it is difficult to determine NbN phases as the diffraction degrees are very close, or even in some cases, the peaks are at the same position which results a superposition and makes it hard to separate from each other. In our study, the deconvulation technique was used for evaluating the phases of the deposited films in XRD analysis and each individual peak was analyzed using Pseudovoight function, a linear combination of Gaussian and Lorentz (Cauchy) profiles, which is discussed in detail elsewhere [31]. Levenberg-Marquardt was used as the fitting method.…”
Section: Methodsmentioning
confidence: 99%